TOWARDS AN ENVIRONMENTAL FINANCE FRAMEWORK: THE CONTRIBUTION OF THE EQUATOR PRINCIPLES: Contribution of the Equator Principles - Mnasri, Khadija; Ben Romdhane, Syrine (Bankers, Markets & Investors, 2025)
The objective of this paper is to study the extent to which the Equator Principles (EPs), in their latest 2019 version, allow for concrete corporate governance commitments to improve the bank's corporate social responsibility strategy. Since their foundation in 2003, the EPs were lauded for integrating social and environmental assessment practices into project assessments. With global climate change, global human rights and social issues have become increasingly prominent, as of the end of 2019, the EPs have been updated to Fourth edition. Our study aims at enriching the debate surrounding the contribution of the EPs to sustainable finance. Overall, the new 2019 version can make a significant contribution to the study of the effectiveness of EPs. EPs have the power to change and control the dynamics and landscape of finance and to rapidly address the challenges of climate change. However, emerging research topics in this area should involve studying the effectiveness of new EP measures in assessing and managing the climate change risk associated with the projects. A recent theoretical and empirical literature review is presented, based on the main research on the contribution of EPs to sustainable finance. However, the literature we currently have on the impact of EP adoption has revealed a lack of empirical research primarily due to the lack of available data. Other emerging research topics in this area should include investigating the effectiveness of new EP measures for assessing and managing project-related climate change risk. However, metrics and standards need to be developed to measure the ecological and climate performance of banks, and this task should be a major challenge.